ChemInform Abstract: Structure, Magnetic and Magnetocaloric Properties of New Nanocrystalline (Pr, Dy)Fe9 Compounds. Issue 38 (September 2016) - Guetari, R.; Bartoli, T.; Cizmas, C. B.; Mliki, N.; Bessais, L.
Abstract: In the view of magnetic refrigeration, the nanostructured pseudobinary alloy samples Pr1‐x Dyx Fe9 (x = 0.0625, 0.125, 0.1875, 0.25) are prepared by high‐energy ball milling of the elements under Ar (5 h) followed by short annealing (Ta foil in evacuated silica tubes, 500—1100 °C, 30 min).